Identification of Nutmeg With Different Mildew Degree Based on HPLC Fingerprint, GC-MS, and E-Nose - Yang, Rui-Qi; Li, Jia-Hui; Feng, Hui-Shang; Yao, Yue-Bao; Guo, Xing-Yu; Yu, Shu-Lin; Cui, Yang; Zou, Hui-Qin; Yan, Yong-Hong (Frontiers in Nutrition, 2022)
Nutmeg (Myristicae Semen), so-called Rou-Dou-Kou in Chinese, is one kind of Chinese herbal medicines (CHMs) as well as a global popular spice. Hence, its stable quality and safe application attracts more and more attention. However, it is highly prone to mildew during storage due to its rich volatile components and fatty oil. Therefore, in this study electronic nose (E-nose) was introduced to attempt to reliably and rapidly identify nutmeg samples with different degrees of mildew. Meanwhile, the chemical composition and volatile oil were analyzed by HPLC fingerprint and GC-MS, respectively, which could support and validate the result of E-nose. The results showed that the cluster results of HPLC fingerprint and GC-MS were generally consistent with E-nose, and they all cluster into two categories. Additionally, discriminant model was established which divided the samples into three categories: mildew-free, mildew-slight and mildew, and a high DPR was obtained, which indicate that the E-nose could be a novel and promising approach for establishment of quality evaluation system to identify CHMs with different degrees of mildew rapidly, especially to identify early mildew.